Cytokine Release Syndrome (CRS) and Nicotine in COVID-19 Patients: Trying to Calm the Storm - Gonzalez-Rubio, Jesus; Navarro-Lopez, Carmen; Lopez-Najera, Elena; Lopez-Najera, Ana; Jimenez-Diaz, Lydia; Navarro-Lopez, Juan D.; Najera, Alberto (Frontiers in Immunology, 2020)
SARS-CoV-2 is a new coronavirus that has caused a worldwide pandemic. It causes severe acute respiratory syndrome (COVID-19), which is fatal in many cases, and is characterized by a cytokine release syndrome (CRS). Great efforts are currently being made to block the signal transduction pathway of pro-inflammatory cytokines in order to control this “cytokine storm” and rescue severely affected patients. Consequently, possible treatments for cytokine-mediated hyperinflammation, preferably within approved safe therapies, are urgently being researched to reduce rising mortality. One approach to inhibit proinflammatory cytokine release is to activate the cholinergic anti-inflammatory pathway through nicotinic acetylcholine receptors (α7nAchR). Nicotine, an exogenous α7nAchR agonist, is clinically used in ulcerative colitis to counteract inflammation. We have found epidemiological evidence, based on recent clinical SARS-CoV-2 studies in China, that suggest that smokers are statistically less likely to be hospitalized. In conclusion, our hypothesis proposes that nicotine could constitute a novel potential CRS therapy in severe SARS-CoV-2 patients.